Features of development of an agricultural warehouse digital twin - Krasnikova, Irina Nikolaevna; Simonov, Vladimir Lvovich; Petelin, Aleksander Evgenievich (BIO web of conferences, 2024)
The article presents the main results of the development of simulation model of agricultural warehouse. Such a model is a digital twin of the real object that reflects all qualitative and quantitative characteristics of objects and included processes. The creation of such digital twin is necessary to assess the effectiveness of the organization of storage, packing, loading and unloading of agricultural products. The relevance of the research lies in the specificity of realization of the above processes due to their intensity depending on the season, microclimatic conditions of the premises, fragility, and short life of products. As a result of using the methods of structural analysis, simulation modeling and graphical method, all key objects and processes of the subject area are established and characterized, behavioral models and three-dimensional visualization of the simulation model are developed.